2020
DOI: 10.1101/2020.05.29.123836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single-cell atlas of the mouse and human prostate reveals heterogeneity and conservation of epithelial progenitors

Abstract: A single-cell atlas of the mouse and human prostate reveals heterogeneity and conservation of 3 epithelial progenitors 4 5 6 Summary 24 Understanding the cellular constituents of the prostate is essential for identifying the 25 cell of origin for benign prostatic hyperplasia and prostate adenocarcinoma. Here we 26 describe a comprehensive single-cell atlas of the adult mouse prostate epithelium, which 27 demonstrates extensive heterogeneity. We observe distinct lobe-specific luminal epithelial 28 populations (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
48
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 57 publications
(21 reference statements)
6
48
1
Order By: Relevance
“…We demonstrate that these RUNX1 + PLCs exhibit a greater organoid forming potential compared to the remaining luminal fraction, consistent with previous reports isolating similar proximal populations using different markers such as SCA-1, TROP2 or CD26 ( Crowley et al, 2020 ; Goldstein et al, 2008 ; Guo et al, 2020 ; Karthaus et al, 2020 ; Kwon et al, 2016 ). Furthermore, RUNX1 + PLCs predominantly formed unipotent K8 + hollow organoids demonstrating their preferential commitment to the luminal fate.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We demonstrate that these RUNX1 + PLCs exhibit a greater organoid forming potential compared to the remaining luminal fraction, consistent with previous reports isolating similar proximal populations using different markers such as SCA-1, TROP2 or CD26 ( Crowley et al, 2020 ; Goldstein et al, 2008 ; Guo et al, 2020 ; Karthaus et al, 2020 ; Kwon et al, 2016 ). Furthermore, RUNX1 + PLCs predominantly formed unipotent K8 + hollow organoids demonstrating their preferential commitment to the luminal fate.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, our adult scRNA-seq dataset highlighted an extensive degree of cellular heterogeneity, in particular within the luminal epithelia. Several studies recently made similar observations either focusing on the AP ( Karthaus et al, 2020 ), the intact prostate ( Crowley et al, 2020 ; Joseph et al, 2020 ), or both the intact and castrated prostates ( Guo et al, 2020 ). Integration of these multiple datasets will provide a more global view of the transcriptional landscape of the prostate epithelium.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…An alternative but not mutually exclusive possibility is that the progressive loss of bipotent luminal progenitors may be associated with a temporal transition in prostate outgrowth from proximal peri-urethral luminal cells to more distal luminal cells. Thus, the transient bipotency of the earliest luminal cells during organogenesis may resemble castration-resistant luminal cells in the proximal region of the adult mouse prostate that are bipotent in organoid and graft assays and have lower AR expression (Crowley et al, 2020;Karthaus et al, 2020;Kwon et al, 2016). Overall, our findings suggest that the requirement for AR function in prostate luminal cells is more limited during organogenesis than in adulthood.…”
Section: Discussionmentioning
confidence: 67%
“…Our findings of a transient bipotent progenitor in prostate organogenesis are consistent with previous evidence that luminal cells can display bipotent properties under non-homeostatic conditions. Luminal cells from adult mouse prostates can generate basal cells when cultured as prostate organoids (Chua et al, 2014;Karthaus et al, 2014;Zhang et al, 2018), and luminal cells can generate basal cells in renal grafts (Crowley et al, 2020;Kwon et al, 2016;Zhang et al, 2018); in addition, rare luminal castration-resistant progenitors in adult prostates can generate basal cells during androgen-mediated prostate regeneration (Wang et al, 2009). In the mammary gland, recent studies have revealed unexpected bipotency of luminal cells during pregnancy or upon hormone stimulation (Song et al, 2019).…”
Section: Discussionmentioning
confidence: 99%